Wykonywanie środka karnego zakazu zajmowania określonego stanowiska a zakaz pełnienia funkcji piastuna organu spółki handlowej - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the issue of executing the penal measure ofprohibition of holding certain positions in relation to the legal consequences of a conviction in the form of a ban on performing functions in a commercial company. The object of study is to present similarities and differences between the two institutions. Consequently, the subject of analysis are issues concerning the initial moments of the two institutions, as well as the circumstances affecting their duration.
Keywords: środek karny; zakaz pełnienia funkcji w spółce handlowej; wykonywanie środka karnego; zakaz zajmowania określonych stanowisk; skutki prawne skazania